Implementation of Moral Education and Transcendental Idealism in MI/SD - M Risdamuddin; Ahmad Padli Prasitya; A Malik; Budiman (Doctoral Program In Elementary Madrasah Teacher Education Faculty Of Tarbiyah And Education - UIN Sunan Kalijaga Yogyakarta, 2025)
Problems often faced by educational institutions recently are often found among students. Several cases that occurred at educational institutions in Bima were specifically related to acts of violence against children/students, either occurring among students or carried out by teaching staff. Cases of beatings experienced by educators are one of the most frequent cases in educational institutions at junior high to high school levels. This situation is a scourge in the teaching and learning process in educational institutions. So special attention is needed in handling this situation by providing character education from an early age so that students with character and morals can be formed. This research aims to determine the process of implementing moral education and transcendental idealism for students at MIN 5 Bima and SD IT Uswatun Hasanah. The method used is qualitative with a multicase study approach. Primary data sources in this research were obtained from two educational institutions, MIN 5 Bima and SD IT Uswatun Hasanah. The results of the research show that there are differences in the implementation of instilling moral values in elementary schools, especially at MIN 5 and SD IT Uswatun Hasanah. These differences show that MIN 5 implements three main activities in instilling moral values in students, namely the Thousand Days Movement. /Infaq for Charity, Tahfid (Memorization of Juz 30), and Health (Environmental Cleanliness) while the results of the activities of instilling moral values at SD IT show that through the program to save adab and ethical values as the formation of student character and morality with a values-based approach Islamic values. These efforts involve all elements in creating a learning environment that supports the positive character and spiritual development of students in the future.